Masculinities and crime - Tomsen, Stephen (Gender and crime, 2024)
This chapter outlines key theoretical developments that have characterized criminological explanations of the widespread link between masculinities and crime. Essentialist and biological views in early criminology were challenged by social analyses stressing sex-role theory and feminist accounts of patriarchy and male violence. From the 1990s, a masculinities paradigm arose from Connell’s theory of “hegemonic” and other masculinities and merged with Messerschmidt’s social interactionist scholarship on crime as “doing masculinity” and its later grounding in a social understanding of masculine bodies. This theorizing has influenced recent approaches, including the stress on life histories, multiple forms of violence, non-violent offending, including crimes of the powerful, the masculinities embedded within prisons, policing and law enforcement, and the uneven and destructive surveillance and criminalization of specific groups of disadvantaged men. Lastly, this chapter reflects on the growing significance of calls for more “intersectional” theorizing and analyses that further develop considerations of racial inequality.